Innovation failure in the eye of the beholder: towards a theory of innovation shaped by competing agendas within higher education. Issue 2 (1st February 2018) - Dudau, Adina; Kominis, Georgios; Szocs, Melinda
ABSTRACT: This paper examines a case of perceived innovation failure in higher education, a service dominated by conflicting institutional logics of professionalism and markets. Through a mixed methodology investigating student attitudes to, and behaviour around, technological innovation, the paper makes a contribution to the public service innovation literature by focusing on duality in innovation outcomes. This is suggestive of an innovation typology in public services: professionalism-driven and consumerism-driven innovation.